False dichotomies: EBM, clinical freedom, and the art of medicine. Issue 1 (15th June 2005) - Parker, M
Abstract : According to numerous commentators, clinical freedom, the art of medicine, and, by implication, a degree of patient welfare, are threatened by evidence based medicine (EBM). As EBM has developed over the last fifteen years, claims about better evidence for medical treatments, and improvements in healthcare delivery, have been matched by critiques of EBM's reductionism and uniformity, its problematic application to individual patients, and its alleged denial of the continuing need for clinical interpretation, insight, and judgment. Most of these attacks on EBM and defences of clinical freedom fail. They are based on erroneous understandings of the relationships between inductive knowledge, clinical uncertainty, and action. Evidence based medicine is a necessary condition for clinical freedom, not a threat to it, and EBM is not something to be balanced with either clinical experience or patient preferences. The art and science of medicine are more conceptually and practically connected than the defenders of clinical freedom, whatever they conceive that to be, are willing to admit.